Unlikely allies: Camel crickets play a role in the seed dispersal of an Asian autotrophic shrub - Kenji Suetsugu; Hirokazu Tsukaya (Plants, People, Planet)
Societal Impact Statement Dust seeds, which are minute and contain minimal energy reserves, are often associated with heterotrophy (plants that obtain carbon without photosynthesis). Consequently, previous studies have mainly focused on the relationships between dust seeds and heterotrophy. However, dust seeds are also found in green plants. This manuscript focuses on the seed ecology of the apparently autotrophic shrub Rhynchotechum discolor that produces dust seeds. Using time‐lapse photography, feeding experiments, and germination tests, we show that camel crickets effectively disperse the seeds of this autotrophic shrub. This is the first study to document insect‐mediated internal seed dispersal of an autotrophic plant in regions inhabited by terrestrial mammals, offering new insights into the evolutionary ecology of dust seeds. Summary Although angiosperms exhibit a wide range of seed sizes, the mechanisms driving these differences are poorly understood. The evolution of dust seeds, which contain minimal energy reserves, is traditionally linked to heterotrophy, in which external carbon sources are provided to the embryo or seedling. Dispersal by small animals may be another important but underexplored evolutionary driver of minute seed size. However, insect endozoochory has been documented only in the seeds of heterotrophic species and autotrophic species in New Zealand (i.e., in communities without native terrestrial mammals). Here, we investigate this seed dispersal mechanism in the Japanese shrub Rhynchotechum discolor (Gesneriaceae), which produces white berries with numerous tiny ellipsoid seeds, using time‐lapse photography, feeding experiments, and germination tests, particularly focusing on potential interactions with insect internal seed dispersers. Our time‐lapse photography indicated that camel crickets predominantly feed on fallen fruits of R. discolor. Field sampling revealed that camel crickets excreted numerous intact R. discolor seeds. Feeding experiments confirmed that some camel crickets excreted a high proportion of intact seeds, many of which successfully germinated into autotrophic seedlings. The present study provides the first evidence of insects acting as endozoochorous seed dispersers in fully autotrophic plants within regions inhabited by terrestrial mammals. Our findings suggest that orthopteran‐mediated seed dispersal is more widespread than previously thought, and that dust seeds can evolve from selective pressures beyond heterotrophy, specifically through insect‐mediated seed dispersal.